PENGARUH IMPLEMENTASI JIT APLIKASI PINJAMAN TERHADAP KINERJA OPERASIONAL DALAM MENINGKATKAN KINERJA PERUSAHAAN (Studi pada Bank BRI pada beberapa KCP di Tembalang Semarang) - Numberi, Yuniati Torsina; Dwiyanto, Bambang Munas (Faculty of Economics and Business Diponegoro University, 2016)
The study about Just in time in association with firm performance has applied in many researches. But, the research that associate Just in time with operating performance and firm performance in service firms was relative rare. The study was aimed to analyze how Just in time Implementation by bank especially in credit process could affect to operating performance and firm performance. Sample of the research is credit analyst in several Cash Office of Bank BRI in Tembalang Semarang. The sample size collected is 42 officers. Instrument of questionnaire is used to collect the data of the research. Multiple regression analysis is applied to prove the hypotheses. Result of the analysis shows that Just in time has positive effect on operating performance. Operating performance also has positive effect on firm performance, and Just in time has positive effect on firm performance.